Download presentation

1
**Equation of Tangent line**

2
**is the negative reciprocal to the slope of the tangent line.**

x2 + y2 = 100 circle 4x – 3y = 50 tangent line (8,6) point of tangency The slope of the radius is the negative reciprocal to the slope of the tangent line. mr = mt = The circle above is defined by the equation: x2 + y2 = 100. A tangent line (4x – 3y = 50) intersects the circle at a point of tangency: (8,6). The tangent line is perpendicular to the radius of the circle. The circle above is defined by the equation: x2 + y2 = 100. A tangent line (4x – 3y = 50) intersects the circle at a point of tangency: (8,6). The tangent line is perpendicular to the radius of the circle. The circle above is defined by the equation: x2 + y2 = 100. A tangent line (4x – 3y = 50) intersects the circle at a point of tangency: (8,6). The tangent line is perpendicular to the radius of the circle. The circle above is defined by the equation: x2 + y2 = 100. A tangent line (4x – 3y = 50) intersects the circle at a point of tangency: (8,6). The tangent line is perpendicular to the radius of the circle.

3
When a tangent and a radius intersect at the point of tangency, they are always perpendicular to each other. It then follows that their slopes are always negative reciprocals of each other. T(0,-3) P(2,-1) C(-1,2) P(2,-1) mr =

4
**Find the slope of the line tangent to the circle x2 + y2 = 5 and passing through the point R(-2,1).**

5
Find the equation of the tangent to the circle x2 + y2 + 10x – 24y = 0 and passing through the point T(0,0). Step 1: Find the centre and the radius. x2 + y2 + 10x – 24y = 0 (x2 + 10x + 25) + (y2 – 24y + 144) = (x + 5)2 + (y – 12)2 = 169 Step 3: Find the slope of the tangent. Centre: (-5,12) r = 13 Step 2: Find the slope of the radius. Step 4: Find the equation of the tangent. 12(y – 0) = 5(x – 0) 12y = 5x 5x – 12y = 0

6
Find the equation of the tangent to the circle x2 + y2 – 6y - 16 = 0 and passing through the point T(3,7). Step 1: Find the centre and the radius. x2 + y2 – 6y - 16 = 0 x2 + (y2 – 6y + 9) = x2 + (y – 3)2 = 25 Centre: (0,3) r = 5 4(y – 7) = -3(x – 3) 4y - 28 = -3x + 9 3x + 4y = 3x + 4y = 37

7
finito

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google